Creating, capturing, and circulating commodities: The technology and politics of material resource flows, from the 19th century to the present. Issue 1 (January 2020) - Veraart, Frank; Åberg, Anna; Vikström, Hanna
Highlights: Resource chains dynamics are embedded in the techno-scientific, geographical, economic, and social developments. Historical analysis is crucial in helping us understand the temporal changes and hidden dynamics of resource chains. Historical analyses of commodity chains show the non-static characteristics of resource activities. The special issue analyses the dynamics of resource chains, influenced by technopolitics, that have shaped todays distribution of global wellbeing and sustainability issues. Abstract: Extractive resources are unevenly distributed geographically and our dependence on such resources is growing, which has led to ever increasing flows of resources across the world. This situation has caused concern for numerous actors. However, such worries are not new. Todays' feel of a deeply interconnected, rapidly changing world with global grand challenges has striking resemblances with the nineteenth century mood in the industrializing countries. In this special issue we study the temporal dynamics and multiple geographies of resource flows, and how actors have attempted to shape and control them. In five articles by historians of technology and the environment from Sweden, Russia and the Netherlands, we aim to broaden the view on resource narratives and emphasize their non-static characters by showing developments of resources as they travel through time and space. This introductory article introduces and positions five themes that are addressed in the contributions of special issue. In this special issue scholars discuss (1) the social construction of resources, (2) the importance of resources to nation states, (3) resource flows as transnational practices, (4) technopolitics of resources, and (5) resource flows as global political power hierarches, of resources such as oil, metals, iron ore, uranium and stone.